(untitled) (International Journal of Engineering and Computer Science, 2017)
In the time of extreme proclivity of users towards internet and its services, it is almost implied to worry for the concerned security of highly confidential information. So, are the available safety trends and the continuous endeavor in this domain towards unfolding new techniques with enhanced features suggest pioneering concerns of the associated parties for preserving the integrity of underlying system(s). Having gone through some of the works available, we can easily gaze at the much talked issues in the field of network business (specifically communication) demanding the robust cryptosystems with adjusting feature(s) to safeguard the interest(s) of communicating parties. It is immaterial to talk about cryptosystems without touching the edges of famous algorithm i.e., R.S.A. algorithm. We, here, attempt to mention a few of the developing techniques that have/are gathering attention from masses associated with this field.